The pharmacokinetics and pharmacodynamics of intravenous hydromorphone in horses. (May 2019) - Reed, Rachel; Barletta, Michele; Mitchell, Krista; Hanafi, Amanda; Bullington, Annie; Knych, Heather; Quandt, Jane; Ryan, Clare; Giguère, Steeve
Abstract: Objective: Describe the pharmacokinetics and pharmacodynamics of intravenous hydromorphone in healthy horses. Study design: Masked, randomized, cross-over, Latin square design. Animals: A group of eight healthy adult horses Methods: Horses were administered each of four treatments with an 8 day washout. Treatments groups included intravenous hydromorphone 0.02 mg kg –1 (LD), 0.04 mg kg –1 (MD), 0.08 mg kg –1 (HD) and saline (P). Blood samples for hydromorphone analysis were obtained for 24 hours after treatment. Plasma hydromorphone was quantified and pharmacokinetic parameters were determined using non-compartmental analysis. Pharmacodynamic data collected for 24 hours after treatment included thermal nociceptive threshold, heart rate (HR), respiratory rate ( f R ) and rectal temperature, and analyzed using mixed-effects linear models. Results: Mean (± standard deviation) hydromorphone terminal half-life ( t 1/2 ), systemic clearance and apparent volume of distribution at steady state (Vdss ) were 18.1 ± 18.6, 34.0 ± 12.8, and 41.3 ± 32.5 minutes, 66.6 ± 5.3, 550.0 ± 76.4, and 92.7 ± 13.9 mL kg –1 minute –1, and 1118 ± 369, 1460 ± 325 and 2242 ± 950 mL kg –1 for treatments LD, MD and HD, respectively. Thermal threshold increased significantly compared to baseline for all treatments for up to 12 hours. HR was elevated above baseline in treatments LD, MD and HD, extending to 30, 15 and 105 minutes after treatment, respectively. Respiratory rate was elevated above baseline in treatments MD and HD from 30 to 195 minutes and from 45 to 480 minutes after treatment, respectively. Temperature was elevated above baseline in treatment HD until 255 minutes after treatment. Conclusions: Hydromorphone exhibited a short t 1/2, rapid clearance and large Vdss in horses. It also provided a dose-dependent increase in thermal threshold with associated increases in HR, f R and rectal temperature. Clinical relevance: Hydromorphone 0.04 mg kg –1 provided clinically relevant thermal antinociception with minimal adverse effects.